2016
DOI: 10.1021/acs.langmuir.5b03559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoclustering and Dipolar Interactions in Heat Generation for Magnetic Hyperthermia

Abstract: Biomedical magnetic colloids commonly used in magnetic hyperthermia experiments often display a bidisperse structure, i.e., are composed of stable nanoclusters coexisting with well-dispersed nanoparticles. However, the influence of nanoclusters in the optimization of colloids for heat dissipation is usually excluded. In this work, bidisperse colloids are used to analyze the effect of nanoclustering and long-range magnetic dipolar interaction on the magnetic hyperthermia efficiency. Two kinds of colloids, compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
106
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 47 publications
5
106
0
2
Order By: Relevance
“…Whilst this model offers an adequate description for single -core nanoparticle systems under consideration of polydispersity, recent work has suggested that so called multi -core particles252627 may be more suited to magnetic hyperthermia. Refs 5, 6, 7, 8, 9, 10 each observe an increase in magnetic heating for multi-core particles compared to single-cores under the same conditions. Multi-core particles consist of several magnetic cores per particle and consequently, long range dipolar interactions within one multi-core particle can be present.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Whilst this model offers an adequate description for single -core nanoparticle systems under consideration of polydispersity, recent work has suggested that so called multi -core particles252627 may be more suited to magnetic hyperthermia. Refs 5, 6, 7, 8, 9, 10 each observe an increase in magnetic heating for multi-core particles compared to single-cores under the same conditions. Multi-core particles consist of several magnetic cores per particle and consequently, long range dipolar interactions within one multi-core particle can be present.…”
mentioning
confidence: 84%
“…Of the many proposed uses of iron oxide nanoparticles the most promising examples are cancer treatment by magnetic hyperthermia567891011, magnetic resonance1213 and particle imaging1415, magnetic biosensing1617 as well as magnetic drug targeting111213. The required magnetic response of the nanoparticles is typically determined by the application, and is in turn intrinsically dependent on the structural properties of the particle system.…”
mentioning
confidence: 99%
“…For those particles in clusters, they are in close contact and are highly interactive. 1 The random and competing interparticle interactions among MNP clusters alter the magnetic dynamic properties by affecting the energy barrier, thence changing the relaxation time and giving rise to a collective magnetic behavior. 2 For this reason, an understanding of the MNP aggregation effect on hyperthermia performance is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Los procesos de generación de calor en las NPM a partir de campos electromagnéticos son bien conocidos, tanto teórica [11], [13], [14] como experimentalmente [15], [16], [17], pero la concordancia entre las observaciones experimentales y las predicciones teóricas no son muy buenas [15], [18], [19]. Esto se debe principalmente a que las NPM están en un entorno altamente interactuante, es decir, una partícula está sometida a interacciones de carácter repulsivo, como la electrostática y la estérica, e interacciones de carácter atractivo, como la la de London-van der Waals.…”
unclassified
“…Si bien, el modelado teórico predice comportamientos del SAR en función de las interacciones dipolares, moduladas por la concentración de NPM en la suspensión, que han sido recientemente confirmados experimentalmente [18], [25], obtener a partir de estos modelos el valor numérico del SAR aún es materia pendiente, una forma de resolver este problema es considerando una energía de activación magnética (o energía de barrera) efectiva, determinada a partir de medidas magnéticas bajo campos estáticos (midiendo la coercitividad en función de la temperatura) o bajo campos dinámicos (midiendo la susceptibilidad magnética en función de la temperatura) [23].…”
unclassified